Bidding for Research Funds. Inter-Fields Differences and Predictors of the Evaluation Scores: Insights from a Romanian National Competition for Postdoctoral Grants - Alin Croitoru; Horațiu Rusu (University Babes-Bolyai, 2021)
This study sought to address an important gap in the existent knowledge about the development of the Romanian research system by looking at a very specific population of young scholars who participated in the national competition for postdoctoral grants (2016) which included over 900 participants. The paper is structured by two main research objectives. Firstly, the analysis if focused on differences between scientific fields by looking at research entities which host young scholars' grant proposals, gender balance, young scholars' academic performance measured through a standardized indicator (Google Scholar H index), share of people trained abroad, and information about the evaluation process. Secondly, a linear regression model is built for the relationship between research proposal's evaluation score and a series of individuals' characteristics and structural factors associated to entities which host young scholars' research proposals. An original database derived from individuals' CVs allows us to test a series of hypothesis and to reveal significant predictors for grant application's evaluation score. For instance, individuals' evaluation score is positively influenced by scholars' higher Google Scholar H Index, short-term and long-term experiences of formal education or training abroad. At the same time, younger participants and women researchers have statistically significant higher scores for their proposals.